BIOPSYCHOSOCIAL APPROACH — A MODERN DEMAND FOR INTERDISCIPLINARITY - E. O. Taratukhin (Российский кардиологический журнал)
The article takes into consideration a novel integrated approach that combines cultural and psychological parts of human being with biological signs of the disease and health. The historical roots from GL Engel are sketched, and some thoughts provided on evaluation and scientific significance of the approach in research and clinical practice.